Seasonal anomalies of stocks in ASEAN equity markets - Kok, Kim Lian; Wong, Yoke Chen * (Sunway University College, 2004)
This study examines the daily anomalies in the five ASEAN equity markets of Malaysia, Singapore, Thailand, Indonesia and the Philippines before, during and after the Asian financial crisis. The regression results reveal different patterns among these markets for each of the three periods. The Monday and Friday effects are most predominant during the pre-crisis period. Only the Tuesday effect in Thailand and the Philippines is observed during the crisis period. While the pattern of daily anomalies in Thailand during the post-crisis period reverts to that of the pre-crisis period, the other four markets exhibit different patterns of daily anomalies compared to the pre-crisis period. When the time-varying return volatility is taken into account through the use of GARCH-M model, the Monday effect remains significant while some of the other daily anomalies have become insignificant during the pre-crisis period. The Tuesday effect in Thailand and the Philippines disappears altogether during the crisis period. Only the Monday and Friday effects in Thailand persist in the post-crisis period.